RELATIONSHIP BETWEEN WAGES AND PRODUCTIVITY OF EMPLOYEES IN COMPANY AGAPIN PRIMA WOOD CILACAP - Purwantiningsih, Dwi; H. Supardi, Drs.; Darini, M.Si., Dra. Sri (Management, 2010)
For labor productivity to increase, needed some incentive to motivate them is one of them by way of a satisfactory wage, therefore companies that want high employee productivity must always consider the level of wages. Linked with these two titles are taken for this research is relationship between wages and productivity of employees in the Company Agapin Prima Wood in Cilacap (Study of Correlation between Wage Work Productivity employees). This study aims to gain knowledge about the relationship of wages to labor productivity, and to gain knowledge that explains the presence or absence of a significant relationship between wages and productivity of employees in the Company Agapin Prima Wood in Cilacap. The theory is used as the basis for a binder in this paper used the theory of justice and two-factor theory of Herzberg. This type of research is associative with the method used is census method because these observations are made to all populations in the production of 240 employees. To collect the necessary data in the study used the method of questionnaire, interview, observation and documentation. The analytical tool used to determine the relationship between wages and productivity of employees in the Company Agapin Prima Wood is the data analysis with descriptive statistics and the Product Moment Correlation Methods. Based on the results obtained show that there are positive and significant relationship between wages (X) with labor productivity (Y) for (r = 644). An increase in wages will lead to increased employee productivity, therefore, the management company must consider the wages given to employees since wages are basic salary and a power stimulant. This can be done by setting wages in accordance with the sacrifice of employees and wages in general in accordance to or greater than UMP. Keywords: Wages, Productivity, Employee.